2015
DOI: 10.1039/c4nr05244g
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance catalyst support for methanol oxidation with graphene and vanadium carbonitride

Abstract: In this study, a graphene-vanadium carbonitride (G-V(C, N)) hybrid is reported as a novel support for the Pt catalyst in methanol oxidation. The catalytic activity of the Pt/G-V(C, N) hybrid for methanol oxidation is greatly enhanced compared with that of a commercial Pt/C catalyst with carbon black as the catalyst support. The outstanding catalytic activity of the Pt/G-V(C, N) catalyst suggests the potential of using graphene-metal carbonitride as the catalyst support in fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…As shown in Figure S4 in the SupportingI nformation, for the PQD MPA sample, the signals of Pb 4p,O1s,N1s,C1s,P2p,S i2p, and Br 3d are clearly observed at 643.6, 531.9, 401.5,2 84.4, 130.6,1 02.3, and 68.7 eV,r espectively. [27] The O1 sspectrum (Figure 6a)f or PQD MPA could be fitted with three peaks:N ÀO at 532.9 eV, [28] P=Oa t5 31.3 eV, [29] and PÀOÀPb at 530.8 eV. [12] The N1ss pectrum (Figure 6b)f or PQD MPA could be fitted with three peaks: ÀNH 3 + at 401.5 eV, [30] CÀNa t4 01.2 eV, [31] ÀNH 2 at 399.7 eV, [30b-d] andN ÀOa t3 99.0 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure S4 in the SupportingI nformation, for the PQD MPA sample, the signals of Pb 4p,O1s,N1s,C1s,P2p,S i2p, and Br 3d are clearly observed at 643.6, 531.9, 401.5,2 84.4, 130.6,1 02.3, and 68.7 eV,r espectively. [27] The O1 sspectrum (Figure 6a)f or PQD MPA could be fitted with three peaks:N ÀO at 532.9 eV, [28] P=Oa t5 31.3 eV, [29] and PÀOÀPb at 530.8 eV. [12] The N1ss pectrum (Figure 6b)f or PQD MPA could be fitted with three peaks: ÀNH 3 + at 401.5 eV, [30] CÀNa t4 01.2 eV, [31] ÀNH 2 at 399.7 eV, [30b-d] andN ÀOa t3 99.0 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[12] The N1ss pectrum (Figure 6b)f or PQD MPA could be fitted with three peaks: ÀNH 3 + at 401.5 eV, [30] CÀNa t4 01.2 eV, [31] ÀNH 2 at 399.7 eV, [30b-d] andN ÀOa t3 99.0 eV. [28,32] Figure 6c shows the Pb 4f spectrum of the samples of PQD MPA ,P QD HPA ,P QD TDPA , Figure 5. Normalized TRPL decay curveso ft he CH 3 NH 3 PbBr 3 perovskitef ilms with APTES and different PAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In comparison with Pt/C catalysts, the potential peak values in both forward and backward scans for the Pt/graphene electrodes are more negative, indicating their superior performance. 23 Figure 6b shows that Pt/graphene electrodes have a better electrocatalytic activity when normalized by Pt loading. Indeed, the chemisorption energy is lower at the interface of graphene and Pt nanoparticles, which in turn enhances the electrolyte diffusion process, and therefore lead to higher activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is further demonstrated that the VN in the 10 % Pt–VN/PGNC composite could improve the electrocatalytic ORR activity because of the synergetic effect between VN and Pt NPs. Based on the above analysis, it can be concluded that the 10 % Pt–VN/PGNC catalyst exhibits more positive onset potential and much larger current than the others, which could be attributed to the synergistic effects of VN, the good conductivity of graphitic carbon, the large specific surface area, the proper pore structures, and to the good contact between VN, Pt, and graphitic nanocarbon.…”
Section: Resultsmentioning
confidence: 91%